Development and Simulation of Stand Alone Photovoltaic Model Using Matlab/Simulink - Himanshu Sharma; Nitai Pal; Yaduvir Singh; Pradip Kumar Sadhu (Institute of Advanced Engineering and Science, 2015)
This paper presents the implementation of a generalized photovoltaic model using Matlab/Simulink software package, which can be representative of PV cell, module for easy use on simulation platform. The proposed model is designed with a user-friendly icon and a dialog box like Simulink block libraries which makes the generalized PV model easily simulated and analyzed in conjunction with power electronics. Taking the effect of sunlight irradiance and cell temperature into consideration, the output current and power characteristics of PV model are simulated and optimized using the proposed model. The proposed model enables the dynamics of PV power system to be easily simulated, analyzed and optimized.